ChemInform Abstract: A Novel and Facile Synthesis of 3, 4‐Diacyl‐2H‐pyran‐2‐ones. New C—C Bond Formation. Issue 47 (3rd November 2016) - Kotali, Antigoni; Nasiopoulou, Despina A.; Harris, Philip A.
Abstract: Applying the ′transformation of a hydroxy into an acyl group′ (TROHIA) concept, 3‐acetyl‐4‐hydroxy‐6‐methyl‐2H‐pyran‐2‐one (i.e., dehydroacetic acid) has been converted into the 3‐acetyl‐4‐aryloyl‐6‐methyl‐2H‐pyran‐2‐ones in 2 steps with excellent yields for the first step but modest yields for the second step only.